Hypoglycemic and hypolipidemic effects of Moringa oleifera leaves and their functional chemical constituents. (15th December 2020) - Chen, Gui-Lin; Xu, Yong-Bing; Wu, Jian-Lin; Li, Na; Guo, Ming-Quan
Graphical abstract: Highlights: Hypoglycemic and hypolipidemic effects of Moringa oleifera leaves (MOLE) were revealed. Fourteen bioactive compounds in MOLE targeting α-glucosidase were identified by UF-LC/MS. Ten bioactive compounds in MOLE targeting pancreatic lipase were detected by UF-LC/MS. The biomolecules in MOLE targeting two enzymes were verified with molecular docking. Key flavonoids in MOLE responsible for hypoglycemic and hypolipidemic effects were probed. Abstract: Moringa oleifera Lam. ( M. oleifera ) leaves have long been consumed as both nutritive vegetable and popular folk medicine for hyperglycemia and hyperlipidemia in Kenya communities. In the current study, in vitro inhibition by M. oleifera leaf extract (MOLE, 90% (v/v) ethanol) of α-glucosidase and pancreatic lipase was demonstrated, followed by determination of the effects of MOLE on both glucose consumption and lipid levels (TC, TG, HDL-C and LDL-C) in 3T3-L1 cells. Potential ligands in MOLE were fast screened using affinity ultrafiltration LC-MS, and 14 and 10 components displayed certain binding affinity to α-glucosidase and pancreatic lipase, respectively. Docking studies revealed the binding energies and hydrogen bonds between potential ligands and enzymes. This study suggests that M. oleifera leaves may be a promising natural source for the prevention and treatment of hyperglycemia and hyperlipidemia as well as a functional food or other product for health care in the near future.